Oralidade nas práticas translíngues: a construção do relato pessoal - Juliotti, Julia (2024)
This article presents the results of an action-research conducted in a Brazilian public school located in a border region between Brazil and Paraguay, aiming to demonstrate how translanguaging and transcultural practices can promote linguistic and cultural diversity in the teaching of Portuguese. By engaging with pedagogical reflections on oral genre instruction and the promotion of diversity in regular educational practices, the study investigated 7th-grade classes in Middle School, adapting the textual genre "personal narrative" into a didactic sequence. The methodology involved analyzing significant moments in which students used orality and writing as complementary practices, contributing to the development of their linguistic and sociocultural skills. The theoretical framework includes literacy and oral genre teaching concepts (Marcuschi, 2010), along with the notions of translanguaging (García & Wei, 2014) and transculturality (Welsch, 1999), providing a foundation to argue that integrating these practices in the classroom fosters comprehensive literacy and the inclusion of different languages and cultures present in the school community. The results show that translanguaging and transcultural practices facilitate the construction of diverse linguistic and cultural identities, enriching the teaching-learning process by valuing linguistic plurality and its modalities. Thus, the study reinforces the importance of orality, even when the final product of a sequence of activities is a written genre.